EVALUATION OF GLADIOLUS VARIETIES FOR FLOWERING AND CUT FLOWER TRAITS UNDER INDO-GANGETIC PLAINS - GIRISH,; P. M.,,; ANJANA SISODIA,; ANIL K. SINGH, (The Bioscan, 2020)
An experiment was conducted at Horticultural Research Farm of the Department of Horticulture, Banaras Hindu University, Varanasi, Uttar Pradesh, India during 2018-19. In this experiment 29 varieties of gladiolus were taken as treatments in a Randomized Block Design with three replications. The variety Chemistry showed early spike emergence (70.88 days), early opening of 1 st , 3 rd and 5 th florets (88.35 days, 88.92 days and 90.40 days, respectively) while, variety Anjali showed late withering of 1 st , 3 rd , 5 th and last florets (109.30, 110.89, 111.75 and 117.70 days, respectively). The variety American Beauty reported maximum length of 1st, 3 rd and 5 th florets (10.90 cm, 10.75 cm and 10.57 cm) and maximum diameter of 1 st , 3 rd , 5 th and last florets (10.55 cm, 10.25 cm, 9.71 cm and 9.18 cm, respectively). The variety Pink Friendship reported maximum flowering duration (14.17 days), maximum number of florets open (15.00) and maximum florets per spike (16.00). Longest spike and inter-node (1 st to 4 th floret) was observed in the variety IIHR (74.06 cm and 15.13 cm, respectively) while, longest rachis was in American Beauty (46.35 cm). The varieties Pink Friendship and American Beauty were found superior to others in this study.